2011
DOI: 10.5152/eajm.2011.38
|View full text |Cite
|
Sign up to set email alerts
|

A Study on the Complications of Surgical Treatment for Bilateral Developmental Dysplasia of the Hip and A Comparison of Two Osteotomy Techniques

Abstract: Objective: This study aims to present a review about complications of surgical treatment of Developmental Dysplasia of the Hip and comparing the kinds and ratios of two osteotomy technique (Salter Innominate Osteotomy and Pemberton Pericapsular Osteotomy).

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
2
0
1

Year Published

2016
2016
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 28 publications
0
2
0
1
Order By: Relevance
“…Developmental dysplasia of the hip (DDH), which is characterized by a shallow acetabulum, shortened femoral neck, excessive femoral anteversion and narrow femoral medullary cavity ( Nakahara et al, 2014 ), may result in a range of complications to the hip joint such as dislocation, focal necrosis, and discrepancies in leg length ( Naci and Kadri, 2011 ). Modular hip system and straight cone femoral stem are usually recommended for the treatment of DDH, due to the free setting of anteversion ( Zhen et al, 2017 ; Wang, 2019 ; Gholson et al, 2020 ), and have shown good postoperative results ( Gholson et al, 2020 ).…”
Section: Introductionmentioning
confidence: 99%
“…Developmental dysplasia of the hip (DDH), which is characterized by a shallow acetabulum, shortened femoral neck, excessive femoral anteversion and narrow femoral medullary cavity ( Nakahara et al, 2014 ), may result in a range of complications to the hip joint such as dislocation, focal necrosis, and discrepancies in leg length ( Naci and Kadri, 2011 ). Modular hip system and straight cone femoral stem are usually recommended for the treatment of DDH, due to the free setting of anteversion ( Zhen et al, 2017 ; Wang, 2019 ; Gholson et al, 2020 ), and have shown good postoperative results ( Gholson et al, 2020 ).…”
Section: Introductionmentioning
confidence: 99%
“…Regarding postoperative complications, we witnessed AVN in 4 hips (4.4%) which was a low rate compared to several studies [2225]. Graft or pin displacement, relocation of osteotomy segments, redislocation of the hip, hematoma, superficial and deep infections, persistent stiffness of the hip joint, femoral fracture, and AVN of the femoral head are examples of postoperative complications of the classic Salter osteotomy [26, 27]. We believe that skeletal traction after adductor tenotomy and iliopsoas release for 1-2 weeks (based on the above-mentioned conditions) and before open reduction and pelvic osteotomy, and also not reefing the capsule after the open reduction, avoid excessive pressure on the femoral head after the surgery, and thereby has significant effects on decrease in rate of AVN.…”
Section: Discussionmentioning
confidence: 98%
“…Gleichzeitig steigt der Druck des Pfannendachs auf die Hüftkopfepiphyse an. In der Folge kann eine Hüftkopfne-krose entstehen [1]. Um diese gefürch-tete Komplikation zu vermeiden, sollte neben einem ausgiebigen weichteiligen Release, bei der häufig gleichzeitig durchgeführten intertrochantären femoralen Umstellungsosteotomie, eine knö-cherne Verkürzung des Femur erfolgen [6].…”
Section: Introductionunclassified